Long-term follow-up of nutritional status in children with GLUT1 Deficiency Syndrome treated with classic ketogenic diet: a 5-year prospective study - De Amicis, Ramona; Leone, Alessandro; Pellizzari, Marta; Foppiani, Andrea; Battezzati, Alberto; Lessa, Chiara; Tagliabue, Anna; Ferraris, Cinzia; De Giorgis, Valentina; Olivotto, Sara; Previtali, Roberto; Veggiotti, Pierangelo; et al. (Frontiers in Nutrition, 2023)
Introduction: The classic ketogenic diet (cKD) is an isocaloric, high fat, low-carbohydrate diet that induces production of ketone bodies. High dietary fatty acid consumption, particularly long-chain saturated fatty acids, could impair nutritional status and increase cardiovascular risk. The aim of this study was to evaluate the long-term effects of 5-years cKD on body composition, resting energy expenditure, and biochemical parameters in children affected by Glucose Transporter 1 Deficiency Syndrome (GLUT1DS). Methods: This was a prospective, multicenter, 5-year longitudinal study of children with GLUT1DS treated with a cKD. The primary outcome was to evaluate the change from pre-intervention in nutritional status, considering anthropometric measurements, body composition, resting energy expenditure, and biochemical parameters as glucose and lipid profiles, liver enzymes, uric acid, creatinine and ketonemia. We conducted assessments at pre-intervention and every 12 months of cKD interventions. Results: KBs increased significantly in children and adolescents, and remained stable at 5-y, according to the diet. No significant differences occurred in anthropometric and body composition standards, as well as resting energy expenditure and biochemical parameters. Bone mineral density have significantly increased during the timecourse according to growing age. Body fat percentage significantly and gradually decreased in line with the increase in body weight and the consequent growth of lean mass. As expected, we found a negative trend in respiratory quotient, and fasting insulin and insulin resistance significantly decreased after cKD initiation. Conclusion: The long-term adherence to cKD had a good safety profile on anthropometric measurements; body composition, resting energy expenditure and biochemical parameters, and we found no evidence of potential adverse effects on the nutritional status of children and adolescents.